MicroRNA-99b-3p promotes angiotensin II-induced cardiac fibrosis in mice by targeting GSK-3β - Yu You-hui; Zhang Yu-hong; Ding Yan-qing; Bi Xue-ying; Yuan Jing; Zhou Hang; Wang Pan-xia; Zhang Li-li; Ye Jian-tao (Acta Pharmacologica Sinica, 2021)
Cardiac fibrosis is a typical pathological change in various cardiovascular diseases. Although it has been recognized as a crucial risk factor responsible for heart failure, there is still a lack of effective treatment. Recent evidence shows that microRNAs (miRNAs) play an important role in the development of cardiac fibrosis and represent novel therapeutic targets. In this study we tried to identify the cardiac fibrosis-associated miRNA and elucidate its regulatory mechanisms in mice. Cardiac fibrosis was induced by infusion of angiotensin II (Ang II, 2 mg·kg−1·d−1) for 2 weeks via osmotic pumps. We showed that Ang II infusion induced cardiac disfunction and fibrosis accompanied by markedly increased expression level of miR-99b-3p in heart tissues. Upregulation of miR-99b-3p and fibrotic responses were also observed in cultured rat cardiac fibroblasts (CFs) treated with Ang II (100 nM) in vitro. Transfection with miR-99b-3p mimic resulted in the overproduction of fibronectin, collagen I, vimentin and α-SMA, and facilitated the proliferation and migration of CFs. On the contrary, transfection with specific miR-99b-3p inhibitor attenuated Ang II-induced fibrotic responses. Similarly, intravenous injection of specific miR-99b-3p antagomir could prevent Ang II-infused mice from cardiac dysfunction and fibrosis. We identified glycogen synthase kinase-3 beta (GSK-3β) as a direct target of miR-99b-3p. In CFs, miR-99b-3p mimic significantly reduced the expression of GSK-3β, leading to activation of its downstream profibrotic effector Smad3, whereas miR- 99b-3p inhibitor caused anti-fibrotic effects. GSK-3β knockdown ameliorated the anti-fibrotic role of miR-99b-3p inhibitor. These results suggest that miR-99b-3p contributes to Ang II-induced cardiac fibrosis at least partially through GSK-3β. The modulation of miR-99b-3p may provide a new approach for tackling fibrosis-related cardiomyopathy.